"I Am a Different Man Now"—Sex Offenders in Circles of Support and Accountability: A Prospective Study. (May 2017) - Höing, Mechtild; Vogelvang, Bas; Bogaerts, Stefan
In Circles of Support and Accountability (CoSA), a group of trained and supervised volunteers support a sex offender (core member in a circle), with the aim of supporting the core member's transitions toward full desistance. A prospective, multi-method design was used to explore psychological and social transitions in core members. Data were collected at the start of their circle, after 6 months, and after 12 months. Qualitative data were collected in semi-structured interviews with 17 core members and a total of 29 professionals, and analyzed with Kwalitan, a computer-assisted program for qualitative data analysis. Quantitative data were assessed with self-report questionnaires for sex offenders. Mean differences between t0, t1, and t2 were tested with repeated-measures ANOVAs. Qualitative results indicated improvements in reflective skills, openness, and problem-solving skills, as well as social skills, agency, and self-regulation. Quantitative results documented improvements in emotion regulation and internal locus of control, and positive trends in self-esteem and coping skills. Due to the small sample size, our results must be interpreted with caution. Core members as well as professionals reported a unique contribution of circles to their process, but this claim needs further confirmation.